Comprehensive Transcriptome Analysis of GS3 Near-Isogenic Lines During Panicle Development in Rice (Oryza sativa L.) - Liang, Wenhua; Hu, Fengqin; Qi, Weicong; Zhao, Chunfang; Chen, Tao; Wang, Cailin; Lv, Yuanda; Zhang, Yadong (Frontiers in Genetics, 2022)
Panicle architecture is an important agronomic trait in rice that affects rice yields and quality. The GRAIN SIZE 3(GS3) locus has been identified as a major quantitative trait locus (QTL) affecting grain length and weight. The current understanding of the function of the GS3 gene, especially concerning the regulatory mechanism of panicle development, is still in its infancy. In this study, we generated GS3 near-isogenic lines (NILs) by successive crossing and backcrossing of TD70 (large grain) with Kasalath (small grain), using Kasalath as the recurrent parent. To identify potential transcription dynamic changes in rice panicle formation and grain shape, we deeply analyzed transcriptional profiles for the NILs (NIL-GS3 and NIL-gs3) at three different panicle developmental stages (S, M, and L). A total of 887, 1,768, and 1,478 differentially expressed genes (DEGs) were identified at stages S, M, and L, respectively. We also found 542 differential expressed long non-coding RNAs (lncRNAs). Co-expression analysis further revealed significant clusters associated with different development periods in NIL-gs3 lines. Gene Ontology and KEGG enrichment analysis revealed G-protein signaling and hormones pathway were successively activated at the M and L stages of NIL-gs3, which indicated activation of the G-protein signaling pathway might trigger the down-streaming hormone signaling transduction. we found that other hormones such ABA, Auxin, CK were significantly enriched in the L stage in the NIL-gs3. We highlighted the synergistic interplay of G-protein and multiple hormones signaling pathways and their essential roles in regulating rice panicle formation and the grain shape. Our study provides an invaluable resource for further molecular mechanistic studies that affect rice grain size and provide new insight for directed selection by marker-assisted backcross breeding.